Transformasi Supervisi Kepala Sekolah dalam Mengintegrasikan Literasi dan Numerasi Lintas Mata Pelajaran di UPT SMP Negeri 32 Gresik - Mazroatun Nisrin; Sri Sundari; Umi Latifah (Edu Journal Innovation in Learning and Education, 2026)
The principal's academic supervision plays a strategic role in improving the quality of learning, particularly in supporting cross-curricular literacy and numeracy integration as demanded by the Merdeka Curriculum. This study aims to analyze the mechanism and effectiveness of principal supervision in supporting literacy and numeracy integration across subjects, identify supporting and inhibiting factors, and analyze the impact of supervision on teacher learning practices at UPT SMP Negeri 32 Gresik. This research employs a qualitative approach with an instrumental case study design. Data were collected through participatory observation, in-depth interviews with the principal, subject teachers, and the vice principal for curriculum, as well as document analysis. Data analysis used the Miles, Huberman, and Saldaña interactive model, while data validity was ensured through source triangulation, method triangulation, and member checking. The results show that: (1) principal supervision is carried out through structured planning, implementation, and follow-up stages with literacy-numeracy integration as an explicit focus; (2) supervision effectiveness reaches approximately 70-75%, characterized by specific and constructive feedback and positive changes in teacher practice; (3) the dominant supporting factors are the principal's visionary and humanistic leadership and solid coordination with the curriculum vice principal, while the main inhibiting factors are time constraints and variation in teacher capacity; and (4) supervision has a positive progressive impact on teacher teaching practices and student literacy-numeracy achievement, as evidenced by an increase of 8.89 points in literacy and 6.67 points in numeracy based on the 2025 Education Report Card. This study confirms that effective supervision is a key mechanism in realizing authentic cross-curricular literacy-numeracy integration in the context of Merdeka Curriculum implementation.